Prevalence and characterization of the elongated styloid process in a population of southern Brazil - Vasconcelos, Irla Milane Souza; Franco, Gilson Cesar Nobre (Seven Editora, 2023)
Objective: the present study aimed to investigate the prevalence of the elongated styloid process by panoramic radiography and characterize them by sex, age, side of elongation, and morphologic.  Materials and Methods: the approach was a retrospective, descriptive study. It analyzed digital medical records and panoramic radiography from 240 subjects over 18 years old. All data were registered with the Odontology Clinic between 2021 and 2022. The exams were performed using panoramic radiography (model Eagle, DABI, Atlante) and the images were analyzed by the software from the equipment. It adopted the morphological classification proposed by Langlais. Finally, it was performed the statistical analyzes. Results: the prevalence of the elongated styloid process was 20,8%, mostly in women, between 18 to 39 years old, bilateral and morphological classification type I.  Conclusion: the present study showed that the elongated styloid process was a common finding, and it should be considered in clinical cases of pain or orofacial discomfort. Therefore, it must disseminate the characteristics and symptoms from the elongated styloid process, mostly for health professionals.DOI:https://doi.org/10.56238/alookdevelopv1-037